A linker strategy for the production and crystallization of Toll/interleukin-1 receptor/resistance protein domain complexes. Issue 5 (15th March 2015) - Williams, Simon J.; Ve, Thomas; Kobe, Bostjan
Abstract : Structural characterization of protein–protein complexes is required to fully understand biological processes. However, such studies can be difficult, particularly when the interactions are transient. In some cases, the covalent linking of weakly interacting binding partners has been shown to facilitate structural studies. Here, we used this approach to investigate, by X-ray crystallography, the interactions between TIR (Toll/interleukin-1 receptor/resistance protein) domains from proteins involved in plant and animal innate immunity. Combinations of TIR domains known to interact were covalently attached using short glycine- and serine-rich linkers. This approach enabled the production of a number of TIR–TIR domain complexes in soluble form, facilitating crystallization studies. Crystallization of two of the tested combinations was achieved. Furthermore, production in soluble form was achieved for another two combinations, where this was not possible for individual proteins. Our results demonstrate that the linker strategy can aid in the structural studies of TIR domains. Similarly, this approach has potential for improving protein production and facilitating structural studies of other protein–protein interaction domains.